STORYTELLING AS A MODERN COMMUNICATION PHENOMENON - Poda Тetiana (Proceedings of the National Aviation University Series Philosophy Cultural, 2022)
Introduction. In the modern world, the technology of storytelling being used in various professional spheres has gained considerable popularity over the past few years. It is one of the most influential tools in the world of social influence. The aim and tasks are to analyze the phenomenon of storytelling as one of the modern information and communication technologies and its application in various social spheres. Research methodology. To achieve the aim the author of the study used a set of basic principles and methods of scientific knowledge: systematic analysis, comparison, critical analysis. Research results. Storytelling is the most relevant tool of text support. Converged text is created by using different sign systems, usually located on several platforms, which allows it to have the characteristics of transmedia and a great communication potential. Transmedia storytelling is extremely relevant in modern communication practices in many spheres of professional activity. The importance of storytelling and its application is taken into account in marketing communications, for example, in advertising and PR. Discussion. Thus, the high efficiency of storytelling as the new communication format has turned it into a relevant marketing tool used in various fields. While writing a success story, one needs to remember five important elements: the plot, the character, the emotions, the details, and the conclusions. Conclusions. Today, the phenomenon of transmedia storytelling attracts special attention not only as a result of the convergence of media formats but also as final evidence of the transition from mass media to interactive multimedia, adapted to a specific recipient and entire network communities. In the modern digital content, the growing role and importance of the visual component of information display and, accordingly, the technical means to ensure its creation, processing, and broadcasting are observed. Storytelling is a flexible tool. There are a huge number of story options for different topics, products, etc. Storytelling is used in education materials. When the story is placed in a visual formula, the result of its action is amplified. That is why visual storytelling is one of the tools that allow one to effectively convey information to the audience and get an emotional response. Thus, in today’s world, storytelling is understood as a communication technology, an effective method of conveying information to the audience, to solve certain problems and ensure effective motivation of the subject to action.